Tourism-Driven Waste and Greenhouse Gas Emissions: A Case Study of Hotels And Culinary Activities in Bukittinggi - Nofriya Nofriya; Arief Sudradjat; Barti Setiani Muntalif; Benno Rahardyan; Kelvianto Shenyoputro (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
The rapid growth of tourism, particularly throughout the hospitality and culinary industries, has intensified municipal waste management issues due to increasing waste volume. Aims: This study aimed to quantify solid waste quantification and greenhouse gas (GHG) emissions assessment from hotels and culinary tourism in secondary urban centers, which contribute to overarching sustainability challenges and guide more effective municipal waste management strategies. Methodology and results: This study employed a quantitative approach by collecting waste data from various types of accommodations and interviews with 450 tourists. GHG emissions were estimated for both accommodation-generated waste and food waste, using relevant emission factors for each category. Among the sampled accommodations, the 4-star hotel recorded the highest average per capita waste generation at 0.411 kg/tourist/day and generated the highest per capita GHG emissions at 0.688 kg CO₂-eq/tourist/day. Rice generated the largest food loss and waste (FLW) at 0.014 kg/tourist/day during the post-harvest phase. FLW from meat resulted in the highest GHG emissions, at 0.023 kg CO₂-eq/tourist/day during the production phase, while FLW from fish generated the highest GHG emissions, at 0.041 kg CO₂-eq/tourist/day in the distribution and marketing phase. Conclusion, significance, and impact study: The findings indicate that higher-class hotels generate greater amounts of waste and associated GHG emissions. In terms of culinary activities, rice contributes most to food loss and waste (FLW), while meat and fish contribute the highest GHG emissions. These quantified results provide an empirical basis for improving municipal waste management and developing targeted climate mitigation strategies in the tourism sector.